Longevity gap and public pensions: A minimal model - András Simonovits (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
The strong and increasing positive correlation between lifetime income and life expectancy (the longevity gap) has recently been widely studied. In this paper we employ the simplest, minimal model to demonstrate the impact of this long-neglected fact on the various types of public pension systems, especially on the issue of progressivity and neutrality.
Keywords: D10; H55; I38; 330; social security; public finance; income-dependent life expectation; longevity gap